ANALISIS DINAMIKA KESEJAHTERAAN PETANI DI PROVINSI JAWA TIMUR - Nurisqi Amalia; Anisa Nurpita (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
East Java province has the largest rice field in Indonesia. East Java can contribute to improving economic growth and reducing poverty. Farmers Exchange Rate (NTP) is one indicator determinant of farmers welfare. NTP is formed from a price index related to inflation, where inflation is also formed from a price change. This study aims to analyze the dynamics of farmer’s welfare in East Java Province observed through quarterly data from 2006 quarter 2 to 2015 quarter 4 with the Vector Error Correction Model (VECM) Method. The results of this study indicate that inflation has the largest proportion and long-term impact in affecting NTP. The interest rate is a variable that affects the NTP with a considerable proportion when compared with the GRDP. Just like inflation, credit interest rates (IR) affect NTP in the long run. Meanwhile, PDRB is the only variable affecting NTP in the short term.